Model for Electromagnetic Information Leakage - Mao Jian; Li Yongmei; Zhang Jiemin; Liu Jinming (Institute of Advanced Engineering and Science, 2014)
Electromagnetic leakage will happen in working information equipments; it could lead to information leakage. In order to discover the nature of information in electromagnetic leakage, this paper combined electromagnetic theory with information theory as an innovative research method. It outlines a systematic model of electromagnetic information leakage, which theoretically describes the process of information leakage, intercept and reproduction based on electromagnetic radiation, and analyzes amount of leakage information with formulas. DOI : http://dx.doi.org/10.11591/telkomnika.v12i2.4010